Integrated System for Dispatching Lifts and Engineering Equipment of Houses - Klimenko, V.P.; Gedz, O.V.; Cespedes Garcia, N.V. (Science and Innovation, 2024)
Introduction. The integrated system for dispatching lists and other engineering equipment of buildings is a hardware and software complex that ensures interaction between individual elements of the system and the central automated workplace of the controller through existing local and global Internet networks. This approach makes it easy to include already existing buildings in the control system and to reduce planning costs when designing new houses. Problem Statement. The lifts cannot be commissioned unless they comply with the minimum requirements of the Regulations for Construction and Safe Operation of Lifts, according to which lifts and machine rooms must be equipped with communication devices and display several signals on the control panel. The cost of such equipment in comparison with the cost of the lifts is negligible, but the problem is the transfer of voice and technological information signals from the lift to the control panel. Purpose. To study the volume and nature of information flows to provide voice communication and transfer of technological information from the lift and other engineering equipment of a modern house, as well as to create hardware and software for dispatching lifts based on the results of the study. Materials and Methods. Applied engineering methods for electronic computer control and information systems for the development of an integrated system for dispatching lifts and engineering equipment of buildings have been used. Results. Hardware and software tools (integrated system for lift dispatching) have been created to ensure the timely response of utilities in the lift dispatching system. Conclusion. The research results can be used to construct real complex computer systems to support the activities of the communal and industrial sectors, as well as in various fields of science and technology.